Suppressing Black Power through Black Panther's neocolonial allegory. Issue 3 (2nd July 2020) - Johnson, Jordan L.; Hoerl, Kristen
ABSTRACT: This essay argues that the superhero movie Black Panther (2018) operates allegorically as a neocolonial text. The central conflict between T'Challa/Black Panther and his nemesis Killmonger maps onto debates and mediated discourses about Black Power ideologies that proliferated during the mid- to late 20th century. The film resolves this conflict through the involvement of a white Central Intelligence Agency agent, paralleling the agency's long history of interventions in the Global South. Ultimately, Black Panther portrays openness to the United States as the best solution to global inequalities caused by colonialism and its attendant racism in the United States. By containing Black political agency within arenas that sustain global inequality, this movie illustrates how inclusion portrayals of Blackness may function as a project of neocolonialism that ultimately maintains whiteness without centralizing white bodies.